2012
DOI: 10.1016/j.tox.2011.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental low-dose bisphenol A exposure leads to early life-stage hyperactivity and learning deficits in adult zebrafish

Abstract: Developmental bisphenol A (BPA) exposure has been implicated in adverse behavior and learning deficits. The mode of action underlying these effects is unclear. The zebrafish model was employed to investigate the neurobehavioral effects of developmental bisphenol A (BPA) exposure. The objectives of this study were to identify whether low-dose, developmental BPA exposure affects larval zebrafish locomotor behavior and whether learning deficits occur in adults exposed during development. Two control compounds, 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
130
4
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(143 citation statements)
references
References 54 publications
8
130
4
1
Order By: Relevance
“…We also found that chronic BPA exposure (across 0-5 dpf) resulted in an inverted U-shaped hyperactivity dose-response curve (Fig. S1A), consistent with previous findings (32). Given that physiological responses to endocrine disruptors are known to be biphasic (10), with elevated responses at nanomolar concentrations, we next asked whether a lower dose of BPA also would cause hyperactive behavior.…”
Section: Bpa Exposure During Hypothalamic Neurogenesis Induces Hyperasupporting
confidence: 89%
See 1 more Smart Citation
“…We also found that chronic BPA exposure (across 0-5 dpf) resulted in an inverted U-shaped hyperactivity dose-response curve (Fig. S1A), consistent with previous findings (32). Given that physiological responses to endocrine disruptors are known to be biphasic (10), with elevated responses at nanomolar concentrations, we next asked whether a lower dose of BPA also would cause hyperactive behavior.…”
Section: Bpa Exposure During Hypothalamic Neurogenesis Induces Hyperasupporting
confidence: 89%
“…1 B and C). Precedents in zebrafish demonstrate that this type of locomotor activity (i.e., hyperactivity burst) can be an indicator of anxiety-like behavior (32,33). We also found that chronic BPA exposure (across 0-5 dpf) resulted in an inverted U-shaped hyperactivity dose-response curve (Fig.…”
Section: Bpa Exposure During Hypothalamic Neurogenesis Induces Hyperasupporting
confidence: 61%
“…Similarly, there has also been a growing interest in characterizing non-social behaviors of zebrafish that may be related to social interaction and may allow better modeling of various human disorders (Seguin et al, 2016). Non-social behaviors that may influence social responses include locomotion, learning, anxiety, and fear responses (Al-Imari and Gerlai, 2008;Bencan et al, 2009;Lee et al, 2010;Maximino et al, 2010;Saili et al, 2012), but how these factors may influence social responses and how they may be regulated by social context remain unexplored.…”
Section: Social Behavior Of Zebrafishmentioning
confidence: 99%
“…The authors also found that these efects are probably not due to an efect on estrogen receptors (or estrogen-like receptors) but may be due to its deleterious efects on the synthesis of key enzyme in steroid hormone synthesis, Aromatase B. This study also demonstrated that developmental BPA exposure led to larval hyperactivity or learning deicits in adult zebraish [90]. There are evidences for temperature-speciic impairment of swimming performance, disturbances in muscle activity and gene expression in zebraish due to exposure of BPA [91].…”
Section: Efects On Nervous System and Behaviourmentioning
confidence: 60%